PENGARUH PRODUCT INNOVATION, LIFE STYLE DAN HEDONIC MOTIVATION TERHADAP PURCHASE DECISION BRAND ZARA (Studi pada Konsumen Jasa Titip Syaza Official) - Mirzagina, Pasya (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2024)
This study aims to analyze the effect of product innovation, life style and hedonic motivation on Zara’s purchasing decision. This study uses data analysis techniques structural modelling (SEM) and data processing Partial Least Sqaure (PLS). The population in this study were consumers who had boughts product from Brand Zara as many as 170 respondents. The sampling technique used was purposive sampling. The result of this study indicate that product innovation has a positive and significant effect on purchasing decision, life style has a positive and significant effect on purchasing decision, and hedonic motivation has a positive and significant effect on purchasing decision.